Transparency and Accountability of School Funds: The Implications for Efficiency and Effectiveness of School Activities - Abdul Rohman; Ahmad Nurkhin; Hasan Mukhibad (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
This study aims to describe the transparency and accountability of school funds. The next objective is to analyze the effect of transparency and accountability of school funds on the efficiency and effectiveness of school activities. The research population is public and private schools in the city of Semarang. The research sample is a school that has been accredited A. The research respondents are school principals, vice principals, and school treasurers. The data collection method used is a questionnaire. Quantitative descriptive analysis and multiple regression analysis were involved to analyze the data. The results of the study show that the level of transparency and accountability in managing school funds is in the good category. The results of multiple regression analysis provide empirical evidence that transparency and accountability have a significant and positive influence on the effectiveness and efficiency of school activities. The practical implication of this study is the importance of increasing transparency and accountability in the management of school funds because it will determine the efficiency and effectiveness of implementing school programs. Involvement of stakeholders in drafting budget and activities school as well as reporting in a manner periodic is an element important in management of school funds. Keywords: Accountability, Efficiency, Effectiveness, School funds, Transparency